Genital pruritus is associated with longer hospital stays, higher costs and increased odds of psychiatric hospitalization among inpatient adults with pruritus in the United States-National inpatient sample (2012-2015) - Siri Choragudi; Luis F. Andrade; Dr. Gil Yosipovitch (Wiley, 2024)
Abstract Background Though a link between pruritus and worse quality of life (QoL) has been established, little research has delved into which type of pruritus is associated with the highest inpatient burden. A better understanding of how pruritus interacts with other conditions may help reduce the length of hospital stays and improve patient outcomes in fields beyond dermatology. Objectives The objective of this study is to determine which type of pruritus disorder is associated with higher inpatient burden (cost and length of stay) and increased odds of psychiatric hospitalization among inpatient adults with pruritus in the United States. Methods We utilized data from the national inpatient sample (NIS) from 2012 to 2015 international classification of diseases, ninth revision, clinical modification (ICD9‐CM). We included male and female adults ≥18 years with primary and secondary diagnoses of pruritus disorders. The outcomes were primary psychiatric diagnosis (yes vs. no), length (days) and the total cost ($) of hospital stay. We explored associations using survey‐weighted binary logistic and linear regression for binary and continuous outcomes and adjusted for covariables (sociodemographic factors). Results Compared with other types of pruritus, prurigo nodularis/lichen simplex chronicus (PN/LSC) (odds ratio [OR] = 2.01; 95% confidence interval [CI]: 1.74,2.33), pruritus ani (OR = 2.83; 95% CI: 1.91,4.21) and genital pruritus (OR = 3.51; 95% CI: 2.96,4.16) had increased odds for hospitalization due to psychiatric reasons. Compared with hospitalized patients with any other type of pruritus, hospitalized patients with genital pruritus had 2.37 higher mean days of hospital stay and $10,644 higher mean total cost. Conclusions Genital pruritus had the highest odds for hospitalization due to a psychiatric disorder, as well as the highest relative increases of average length and cost of hospital stay compared with the five other types of pruritus diagnoses in ICD9‐CM.